For x = 3 and y = -2, verify that
(x-y)^3 = x^3 - y^3 - 3xy (x-y)
Answers
Answered by
19
Answer:
Given,
x = 3
y = -2
Find,
Verify it (x-y)³ = x³ - y³ - 3xy (x-y)
Step-by-step explanation:
So,
x = 3 and y = -2, verify that (x-y)³ = x³ - y³ - 3xy (x-y)
We get,
=> (3-(-2))³ = 3³ -(-2)³ -3*3*(-2)(3-(-2))
Or. (3+2)³ = 27 -(-2)(-2)(-2) - (-18) (3+2)
Or. 5³ = 27-(-8) + 18 * 5
Or. 125 = 27 + 8 + 90
Or. 125 = 125
Hence,
(x-y)³ = x³ - y³ - 3xy (x-y) is verified for x = 3 and y = -2
Answered by
8
Given
- x = 3
- y = -2
To verify
- (x - y)³ = x³ - y³ - 3xy (x - y)
Solution
- [3 - (-2)]³ = 3³ - (-2)³ - 3(3)(-2) (3 - (-2)
- [5]³ = 27 - (-8) - 3(3)(-2)(5)
- 125 = 27 + 8 + 90
- 125 = 125
- L.H.S = R.H.S
Learn these
- (a + b)³ = a³ + b³ + 3ab (a + b)
- (a - b)³ = a³ - b³ - 3ab (a - b)
- a³ - b³ = (a - b) (a² + b² + ab)
- a³ + b³ = (a + b) (a² + b² - ab)
Similar questions
Science,
2 months ago
English,
2 months ago
Science,
5 months ago
English,
1 year ago
Social Sciences,
1 year ago